2004
DOI: 10.1002/eji.200425196
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the stratum corneum allows potent epicutaneous immunization with protein antigens resulting in a dominant systemic Th2 response

Abstract: The skin is an important immunological organ with an outer protective layer, the stratum corneum forming a barrier between the skin-associated lymphoid tissue and the environment. We show that gently removing the stratum corneum with adhesive tape permits potent epicutaneous immunization to protein antigens. IL-4 secretion by T cells from draining lymph nodes and high levels of specific IgE and IgG1 with no IgG2a showed that the immune responses induced following epicutaneous antigen exposure are strongly Th2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
190
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(203 citation statements)
references
References 41 publications
7
190
2
4
Order By: Relevance
“…Our results show robust expression of IFN-g, IL-2 and TNF-a in CD4 1 T cells after immunization with HEL and CT, whereas IL-4 and IL-5 were not detectable, which is in contrast with previous reports that indicated a Th2 cytokine response after ear immunization [10,11]; this also argues against the occurrence of dominant Th2 responses toward antigens that are coadministered with CT in mucosae [16,17]. In the skin, both Th1 and Th2 cytokines have been reported following immunization with OVA and CT [24].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results show robust expression of IFN-g, IL-2 and TNF-a in CD4 1 T cells after immunization with HEL and CT, whereas IL-4 and IL-5 were not detectable, which is in contrast with previous reports that indicated a Th2 cytokine response after ear immunization [10,11]; this also argues against the occurrence of dominant Th2 responses toward antigens that are coadministered with CT in mucosae [16,17]. In the skin, both Th1 and Th2 cytokines have been reported following immunization with OVA and CT [24].…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that LCs remain in the epidermis for 48 h, even in the presence of Th1-polarizing adjuvants [7]. In our experiments, 24 h after CT or CTB inoculation in the ear, the number of LCs in the epidermis was reduced, suggesting that LCs could be mobilized from the dermis at this time point in the presence of strong adjuvants such as CT.Our results show robust expression of IFN-g, IL-2 and TNF-a in CD4 1 T cells after immunization with HEL and CT, whereas IL-4 and IL-5 were not detectable, which is in contrast with previous reports that indicated a Th2 cytokine response after ear immunization [10,11]; this also argues against the occurrence of dominant Th2 responses toward antigens that are coadministered with CT in mucosae [16,17]. In the skin, both Th1 and Th2 cytokines have been reported following immunization with OVA and CT [24].…”
contrasting
confidence: 92%
See 2 more Smart Citations
“…This barrier disruption process is painless, highly effective in augmenting the transfer of macromolecules such as proteins or DNA into skin, and has been successfully utilized in human clinical trials. 46,[48][49][50] An additional advantage is that physical barrier disruption itself has been shown to trigger activation of keratinocytes and LCs in skin, providing some level of 'built-in' adjuvant response. [44][45][46][49][50][51][52] We thus tested a model where the dorsal ears of anesthetized mice were tape-stripped followed by application of as-assembled, airdried (Poly-1/ova) 40 films on either glass or PDMS substrates, fixed in place by surgical tape against the exposed ear skin, mimicking a common strategy used in skin vaccination studies 45,46 (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%